Structural analysis and construction quality assessment of a free-form ice composite shell. (October 2020) - Wu, Yue; Liu, Xiuming; Luo, Peng; Zhang, Ruinan
Abstract: The large-span ice composite shell structure constructed by inflatable formwork and cellulose-water mixture spraying method brings a new aesthetic activity to the conventional ice and snow buildings. How to ensure the structural safety of large-span ice shells and satisfy the serviceability in the operation stage has become an urgent problem for structural engineers. Based on the Koi-fish ice shell structure constructed in winter at Harbin Ice-Snow World, China, exhaustive structural investigations on the behaviour of the ice composite shell under multiple load conditions are conducted. Subsequently, the construction quality of the ice shell after completion is discussed and evaluated. The results show that temperature action is the main factor affecting the structural safety of the ice shell. Construction assessment results show that the practical ice shell structure can satisfy the design safety requirements.